THE IMPLEMENTATION SCHOOL BASIC MANAGEMENT EFFORT DEVELOPING STRATEGY TO STUDENT COMPENTENCY AT SMAN 1 KAMANG MAGEK KABUPATEN AGAM - Abdul Istiqlal; Afdhal Rinsik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
Current educatioan is getting more challenges, one of which is that education takes place in a setting made-up environment, since it should foster behavior which is useful for individual in the future, not now. As a result of setting an artificial envorment is a fun learning atmosphere. Another problem facing by the world of education is schools are aversive, where the students, teachers, vice headmaster, and headmaster, especially to student competency, manajement school basic, and developing strategy. This research strated form the low guality of education at SMAN 1 Kamang Magek kabupaten Agam. The purpose this research is to know the implementation school basic management effort developing strategy to student competency at SMAN 1 Kamang Magek. The subjects in this research were 46 teachers, vice headmaster and headmaster. Which is where the researcher served as head as school years 2021/2022. Action is implemented in 3 cycles. In the implantation of the action, the design is done in 3 cysles that include; (1) planning, (2) action, (3) obervastion, (4) reflection. In the data collection techigues used are to use observations and guestionnaires. This was apparent at the first meeting of the 46 teachears, vice headmaster and headmaster who were percent (%) at the study : cyle 1 : 56, 62 %, increased to cycle 2 : 78, 34 %, and in cycle 3 increased to 82, 56 %, This the hypothesis proposed above is acceptable.